Properties of polypropylene fiber reinforced concrete using recycled aggregates - Akca, Kutalmis Recep; Cakir, Ozgur; Ipek, Metin (ELSEVIER SCI LTD, 2015)
In this study, recycling of rubble obtained during urban transformation and manufacturing new concrete using this material was experimentally studied. Different combinations were generated using the recycled concrete aggregates and polypropylene fiber. Natural aggregates were replaced by recycled concrete aggregates (RCAs) and volume of 0%, 1% and 1.5% fiber were introduced for each series. Although concretes' physical and mechanical properties were affected negatively by RCA due to RCA's higher porosity and water absorption capacity, high strength concrete was eventually manufactured. Additionally, although fiber content increases flexural properties, there is no significant difference observed between 1% and 1.5%. Percentage contribution ratios of parameters which influence the results of experiments were also calculated by means of analysis of variance (ANOVA) method. As the result of ANOVA which is carried out on specimens containing fiber and recycled concrete aggregate, main factor on changes of compressive strength were determined as aggregate type, while fiber content were also influential on flexural and splitting tensile strength besides aggregate type. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Urban transformation; Recycled aggregate; Fiber; ANOVA; MECHANICAL-PROPERTIES; CONSTRUCTION; MANAGEMENT; STRENGTH; BEHAVIOR; WASTE; Construction & Building Technology; Engineering; Materials Science